1982
DOI: 10.1002/app.1982.070270631
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and deformation rate on the hot-drawing behavior of porous high-molecular-weight polyethylene fibers

Abstract: SynopsisThe nature of the deformation process involved in hot drawing of porous high-molecular-weight polyethylene was examined by apparent elongational viscosity measurements at drawing temperatures between 100°C and 150°C and deformation rates in the range of 10-6-10-3 m/s. The temperature dependence of the apparent elongational viscosity revealed three distinguishable intervals with different activation energies. In the range of 100-133"C, the activation energy amounted to 50 kJ/mol, indicating that hot-dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 1 publication
1
52
0
3
Order By: Relevance
“…A completely different mechanism at 144 ~ C, as previously suggested [18], is clearly demonstrated in Figs. 5 and 6, although a more or less isotropic filament was used in our case.…”
Section: Relation Between Morphology and Flow Properties Of Gel-spun supporting
confidence: 63%
See 2 more Smart Citations
“…A completely different mechanism at 144 ~ C, as previously suggested [18], is clearly demonstrated in Figs. 5 and 6, although a more or less isotropic filament was used in our case.…”
Section: Relation Between Morphology and Flow Properties Of Gel-spun supporting
confidence: 63%
“…In a subsequent series of experiments on the filament A, the drawing temperature was increased to 144 ~ C. This temperature can be considered to b e close to the lower bound of the optimum hotdrawing range established for the preparation of ultra-strong polyethylene fibres [18]. Drawing in this range is accompanied by migration and removal of defects and by an increase in crystal continuity [19].…”
Section: Deformation Of An As-extruded Filamentmentioning
confidence: 86%
See 1 more Smart Citation
“…Several authors [16,[18][19][20][21][22] reported that the drawing temperature and rate could markedly affect the maximal achievable draw ratio and tensile properties of solution-grown UHMWPE samples. In addition to the gel solution compositions and drawing conditions, it is generally recognized that the conditions used in the formation process after spinning and/or solution casting of gel solutions can also have a significant influence on the morphology, microstructure and drawing properties of the specimens formed during the above mentioned processes [2,19,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…These fibrillar structures may be more or less closely packed depending on, for example, molecular weight and drawing conditions. For relatively low drawing temperatures, very loosely packed fibrillar structures are obtained, whereas higher draw- ing temperatures result in more dense structures due to melting/recrystallization [28][29][30][31][32]. The drawing temperature commonly used in our laboratory is in the range 144 to 148~ During drawing at these temperatures the porosity on a 100rim scale is largely eliminated [24,30,33].…”
Section: Voids In Hot-drawn Gel-spun Polyethylene Fibresmentioning
confidence: 99%